Designer Exosomes for Active Targeted Chemo‐Photothermal Synergistic Tumor Therapy - Wang, Jie; Dong, Yue; Li, Yiwei; Li, Wei; Cheng, Kai; Qian, Yuan; Xu, Guoqiang; Zhang, Xiaoshuai; Hu, Liang; Chen, Peng; Du, Wei; Feng, Xiaojun; et al. (Advanced functional materials, 2018)
Exosomes, naturally derived nanovesicles secreted from various cell types, can serve as an effective platform for the delivery of various cargoes, because of their intrinsic ability such as long blood circulation and immune escapinge. However, unlike conventional synthetic nanoparticles, drug release from exosomes at defined targets is not controllable. Moreover, endowing exosomes with satisfactory cancer‐targeting ability is highly challenging. Here, for the first time, a biological and synthetic hybrid designer exosome is described with photoresponsive functionalities based on a donor cell‐assisted membrane modification strategy. Practically, the designer exosome effectively accumulates at target tumor sites via dual ligand‐mediated endocytosis. Then the localized hyperthermia induced by the conjunct gold nanorods under near‐infrared irradiation impacts the permeability of exosome membrane to enhance drug release from exosomes, thus inhibiting tumor relapse in a programmable manner. The designer exosome combines the merits of both synthetic materials and the natural nanovesicles. It not only preserves the intrinsic functionalities of native exosome, but also gains multiple abilities for efficient tumor targeting, controlled release, and thermal therapy like synthetic nanocarriers. The versatile designer exosome can provide functional platforms by engineering with more multifarious functionalities from synthetic materials to achieve individualized precise cancer therapy in the future. A biological and synthetic hybrid designer exosome is presented with photoresponsive functionalities based on a donor cell‐assisted membrane modification strategy. The dual ligand engineered exosomes are shown to significantly increase accumulation at the target tumor site and can burst release drug under controllable near‐infrared irradiation in vitro and in vivo.